The effects of sub-allotment system on the fund allocation and fiscal responsibility among the district hospitals in the Province of Iloilo a policy research - Anuevo, Orwen M. (2005)
This descriptive study purports to identify the effects of Sub-allotment System on the fund allocation and fiscal responsibility among the district hospitals in the Province of Iloilo. Specifically, the following questions are answered : 1) How are district hospital funds being allocated to the District Hospitals? 2) How are the funds being managed to meet the operations requirement of the District Hospitals? 3) How the District Hospitals address various problems brought by the sub-allotment system?. There are 42 respondents, majority of them are 25 to 35 years old age group and (67%) are female, respondents include the chief of hospital, administrative officer, cashier/bookkeeper and accountant of district hospitals. Those who will be subject to in depth interview or study will be selected purposively using the result of the survey. Primary data was generated through interviews, schedules, group discussions and conduct of survey questionnaires. Results were tabulated and presented in tabular format for ease of presentation and analyzed using descriptive statistics, particularly frequency distribution and percentaging. Result of the study revealed that the sub-allotment system has enabled the district hospitals to manage their own funds. They can now disburse funds independent from the provincial capitol. Disbursements like payment for salaries, allowances, travel expenses and foods for the patients are now done in the hospital. It also enabled thedistrict hospital to prioritize their expenses with a corresponding fund allocation. The sub-allotment system in the district hospitals defines the fiscal responsibilities of the persons who has direct role in hospital fiscal administration. The following are the formulated recommendations to address the problems stated : 1) Re-evaluation of the sub-allotment system implemented in the district hospitals to take into consideration the current development in hospital health care system. 2) Apply full and not partial sub-allotment to the district hospitals, 3)Accrue 50% of all hospitals collections to the hospitals for the advancement of facilities and to ensure supplies availability. 4) Sangguniang Panlalalwigan to amend the Philhealth Collection Utilization Ordinance to included drugs and medicines in Philhealth Collection Utilization, 5) Sangguniang Panlalawigan to give authority to districthospitals to accept consignments goods such as medical and surgical supplies, and drugs and medicines from legitimate drug and medical companies, 6) Decentralized the procurement process and empower the hospital management, 7) Deposit hospital collections to their depository banks where they maintained their current accounts and to draw checks payable to the provincial treasury for the remittance of hospital collections, and 8) the provincial government should mobilize the internal control division of the provincial accountant's office to give more attention to the fiscal administration in the district hospitals.
[Research Paper] (Mgt 299). -- [Iloilo City] : UPV-CM, March 2005.